Temporal trends and survivorship of total hip arthroplasty in very young patients: A study using the NJR data set - Metcalfe, D; Peterson, N; Wilkinson, M; Perry, DC (British Editorial Society of Bone and Joint Surgery, 2018)
Aims The aim of this study was to describe temporal trends and survivorship of total hip arthroplasty (THA) in very young patients, aged ≤ 20 years. Patients and Methods A descriptive observational study was undertaken using data from the National Joint Registry (NJR) for England, Wales, Northern Ireland and the Isle of Man between April 2003 and March 2017. All patients aged ≤ 20 years at the time of THA were included and the primary outcome was revision surgery. Descriptive statistics were used to summarize the data and Kaplan–Meier estimates calculated for the cumulative implant survival. Results A total of 769 THAs were performed in 703 patients. The median follow-up was 5.1 years (interquartile range (IQR) 2.6 to 7.8). Eight patients died and 35 THAs were revised. The use of metal-on-metal (MoM) bearings and resurfacing procedures declined after 2008. The most frequently recorded indications for revision were loosening (20%) and infection (20%), although the absolute risk of these events occurring was low (0.9%). Factors associated with lower implant survival were MoM and metal-on-polyethylene (MoP) bearings and resurfacing arthroplasty (vs ceramic-on-polyethylene (CoP) and ceramic-on-ceramic (CoC) bearings, p = 0.002), and operations performed by surgeons who undertook few THAs in this age group as recorded in the NJR (vs those with five or more recorded operations, p = 0.030). Kaplan–Meier estimates showed 96% (95% confidence interval (CI) 94% to 98%) survivorship of implants at five years. Conclusion Within the NJR, the overall survival for very young patients undergoing THA exceeded 96% during the first five postoperative years. In the absence of studies that can better account for differences in the characteristics of the patients, surgeons should consider the association between early revision and the type of implant, the number of THAs performed in these patients, and the bearing surface when performing THA in very young patients.